Technology evaluation in medical electronics equipment/systems industry : a report prepared under Programmes Aimed at Technological Self Reliance (PATSER (Series) ;, 1992)
Based on the consultant's study and deliberations of Interaction Meeting on Technology Evaluation in Medical Electronics Equipment and Systems held on 21st July 1992 at New Delhi.